2021
DOI: 10.1155/2021/3400329
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of African Fermented Indigenous Vegetables in Maternal and Child Nutrition in Sub-Saharan Africa

Abstract: Hunger and malnutrition continue to affect Africa especially the vulnerable children and women in reproductive age. However, Africa has indigenous foods and associated traditional technologies that can contribute to alleviation of hunger, malnutrition, and communicable and noncommunicable diseases. The importance of African indigenous vegetables is undeniable, only that they are season-linked and considered as “food for poor” despite their high nutritional contents. The utilization of African indigenous vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Of all the twentyone (21) phytochemical compounds detected as naturally occurring in leaves of C. dregei, only resorcinol, though present in small amounts, was found to have mild toxicity [47]. This fermentation process eliminated the resorcinol toxicity concern, which is expected since fermentation was reported to improve the safety of foods [48]. This study also revealed chlorogenic acid can be biosynthesized from ferulic acid and 1,3,4-Trihydroxy-5-oxocyclohexanecarboxylic acid (Pg5-1), and vice versa.…”
Section: Phytochemical Constituents In the Leaves Of The Fermented C ...mentioning
confidence: 87%
“…Of all the twentyone (21) phytochemical compounds detected as naturally occurring in leaves of C. dregei, only resorcinol, though present in small amounts, was found to have mild toxicity [47]. This fermentation process eliminated the resorcinol toxicity concern, which is expected since fermentation was reported to improve the safety of foods [48]. This study also revealed chlorogenic acid can be biosynthesized from ferulic acid and 1,3,4-Trihydroxy-5-oxocyclohexanecarboxylic acid (Pg5-1), and vice versa.…”
Section: Phytochemical Constituents In the Leaves Of The Fermented C ...mentioning
confidence: 87%
“…One of the ways vegetables are consumed is in their fermented form. Mostly lactic acid and alkaline fermentation occurs when vegetables are fermented [228]. Lactic acid fermentation can occur in vegetables when conditions are suitable (anaerobic conditions, suitable temperature, and humidity and salt concentrations).…”
Section: Fermented Vegetablesmentioning
confidence: 99%
“…), amaranth (Amaranthus spp. ), cowpea leaves and pods (Vigna unguiculata), spider plant (Cleome gynandra), mallow jute (Corchorus olitorius), African kale, (Brassica carinata), moringa (Moringa oleifera), and pumpkin leaves (Cucurbita muschara) [15].…”
Section: Introductionmentioning
confidence: 99%